The Effect of Work Systems, Work Environment, and Work Motivation to Employee Work Discipline : Case Study of Attendance System at University of Muhammadiyah Jember - Aisyah Kurnia Yuliastutik; Muhamad Naely Azhad; Jekti Rahayu (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to determine and analyze the extent to which the effect of the fingerprint attendance work system, work environment, and work motivation to work discipline. The hypothesis in this study is the fingerprint attendance work system, work environment, and work motivation partially influence work discipline. The object of this research is the employees of the Muhammadiyah University Jember which has a total population of 240 people using the proportionate stratified random sampling technique. Data collection techniques using observation and questionnaires. The analysis used is the validity test, reliability test, multiple linear regression analysis, normality test, multicollinearity test, heteroscedasticity test, linearity test, autocorrelation test, t-test, and coefficient of determination. The results showed that the work attendance system was not significant for work discipline, work environment, and work motivation had a positive and significant effect on work discipline.